2002
DOI: 10.1086/502000
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Hemodialysis-Associated Primary Bloodstream Infections: The Experience of Ten Hospital-Based Centers

Abstract: Primary BSI rates varied widely among participating centers and declined during the study period. BSIs were strongly associated with central venous catheter access. Further studies are needed to determine the reasons for variance in rates between centers and among various types of hemodialysis access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
3
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 8 publications
5
44
3
2
Order By: Relevance
“…A study 16 that aimed to identify the incidence of infection and evaluate the profi le of microorganisms isolated showed that 35% of bacteremic episodes were caused by gramnegative bacteria, a rate consistent with those reported in other studies [17][18][19] . Other study that use the medical records of 239 patients undergoing hemodialysis at the Department of Nephrology of the University Hospital of Heraklion, Crete, Greece, identify that, 3 out of 8 isolated (37.5%) Enterobacter spp.…”
Section: Discussionsupporting
confidence: 74%
“…A study 16 that aimed to identify the incidence of infection and evaluate the profi le of microorganisms isolated showed that 35% of bacteremic episodes were caused by gramnegative bacteria, a rate consistent with those reported in other studies [17][18][19] . Other study that use the medical records of 239 patients undergoing hemodialysis at the Department of Nephrology of the University Hospital of Heraklion, Crete, Greece, identify that, 3 out of 8 isolated (37.5%) Enterobacter spp.…”
Section: Discussionsupporting
confidence: 74%
“…In a second surveillance study, Dopirak et al 5 determined rates of BSI among patients at 10 dialysis centers in Connecticut during 1999 to 2000. The Centers for Disease Control and Prevention (CDC) definition for primary BSI was used.…”
Section: Jerome I Tokars Md Mphmentioning
confidence: 99%
“…In studies of hemodialysis patients, BSI rates have been expressed as infections per 1,000 patient-days, 1,000 dialysis sessions 3 3 Dopirak et al 5 Stevenson et al 7 Tokars et al 8 Price et al 4 erally have 3 hemodialysis sessions per week), 100 patientmonths, 4 ' 8 or 100 patient-years 4 ; all express the same concept, and rates are easily converted from one denominator to another. In the CDC surveillance system, the number of patients at risk is determined only once a month.…”
Section: Jerome I Tokars Md Mphmentioning
confidence: 99%
“…Unfortunately, few dosing schemes have been developed for patients receiving high-flux hemodialysis (HFHD). Furthermore, bloodstream infections are common in hemodialysis patients, with Gram-negative bacilli accounting for 14 to 43% of these events (3)(4)(5)(6). With few new drugs for Gram-negative bacilli on the horizon, optimization of potent drugs with activity against Gramnegative organisms, such as ceftazidime, is now more important than ever.…”
mentioning
confidence: 99%